An Integrated Outsourcing Framework: Analyzing Boeing's Outsourcing Program for Dreamliner (B787). (January 2014) - Elahi, Ehsan; Sheikhzadeh, Mehdi; Lamba, Narasimha
<x xml:space="preserve">Abstract</x> This paper analyzes the outsourcing model that Boeing devised to develop its latest commercial airplane model: Dreamliner (B787). The development of this airplane, which seemed to be very promising in the beginning, turned into the longest delayed program in the history of the company. In this paper, we propose an integrated outsourcing framework through which we try to find the root causes of the delays and the resulted extra costs. The proposed framework shows how the interaction of all influential factors in four outsourcing dimensions (who, what, to whom, and how) determines the performance of an outsourcing program. Copyright © 2014 John Wiley & Sons, Ltd.